Safarnāmah-i junūb-i Īrān - Babin, Claude (Silsilah-'i nutun va taḥqiqāt ; Farhang-i Īrān zamīn ;, 1985)
Travel impressions of southern Iran, 1885, by the author and his compatriot Frederic Adolphe Célestin Arsene Houssay, 1860-1920; translated and annotated by Muḥammad Ḥasan Khān I'timād al-Salṭanah.